1984
DOI: 10.1039/dt9840002467
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physico-chemical properties of the ternary complexes formed between adenosine 5′-triphosphoric acid, bis(2-pyridyl)amine, and divalent metal ions. Crystal and molecular structures of the compounds containing MgIIand CaII

Abstract: Ternary compounds formed between M (Mg", Ca", Sr", Mn", Co", Cu", or Zn"), adenosine 5'-trip hosp ha te [adenosine 5'trip hosp hate (4 -) = atp] , and bis (2pyridyl ) amine (bi pyam) have been prepared. The solid compounds are crystalline and have a stoicheiometry described by the formula M (Hatp) ( Hbipyam).nH20 (n = 2-9). X-Ray powder diffraction patterns are similar. Potentiometric titrations in aqueous solution show the presence of t w o ionizable protons. Visible spectra suggest an octahedral co-ordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 5 publications
7
46
2
Order By: Relevance
“…This is indicative of a phosphate coordination mode in this series of metal-ATP complexes. The coordination of the a, P, and y phosphate oxygen atoms in M~~+ and ca2+ in several other ternary metal-ATP complexes is known from X-ray crystallography (9,10). In the spectra of the Pt-ATP complexes prepared here, the vibrations related to the phosphate group exhibited no major changes upon metal complexation (Fig.…”
Section: Nuclear Magnetic Resonance Spectramentioning
confidence: 92%
See 2 more Smart Citations
“…This is indicative of a phosphate coordination mode in this series of metal-ATP complexes. The coordination of the a, P, and y phosphate oxygen atoms in M~~+ and ca2+ in several other ternary metal-ATP complexes is known from X-ray crystallography (9,10). In the spectra of the Pt-ATP complexes prepared here, the vibrations related to the phosphate group exhibited no major changes upon metal complexation (Fig.…”
Section: Nuclear Magnetic Resonance Spectramentioning
confidence: 92%
“…2 and Table 4). A recent structural analysis of Mg2+ and Ca2+ complexes of ATP and dipyridineamine also exhibited the C2'-endo-anti sugar conformation in these metal complexes (10). It is interesting to note that in the ternary compounds of ATP with Cu2+ and zn2+, the sugar has C3'-endo-anti conformation (7,8), whereas in the corresponding binary complexes the sugar showed the C2'-endo-anti conformation (Table 4).…”
Section: Nuclear Magnetic Resonance Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for the synthesis and preparation of crystals suitable for X-ray diffraction studies was similar to that previously reported [12,13]. Crystalline DPA (34 mg, 0.2 mmol) was added by 3 mL EtOH (95% v/v) and the clear 2) were selected through the polarizing microscope, mounted on a thin glass fiber and then submitted to X-ray diffraction experiments.…”
Section: Synthesis Crystal Growth and X-ray Studiesmentioning
confidence: 99%
“…/Ca 2+ -adenosine 5'-triphosphate, Mg/CaATP, that have linking interactions between the metal ions and the nucleo-tide molecule via the phosphate oxygen only, previously reported [12,13], were studied with the aim to shed light on the role of free water molecules. Room temperature data collection were done via a conventional source Siemens P4 diffractometer, and (in subsequent data collections) by using a Bruker Nonius FR 591 rotating anode with molybdenum target and a Nonius Kappa CCD with confocal focusing mirrors.…”
Section: +mentioning
confidence: 99%